Does Islamic banking contribute to the application and implications of the green economy in central Asian countries? - Sharofiddin, Ashurov (REDmoney Group, 2023)
Central Asian nations such as Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan and Uzbekistan have acknowledged the importance of transitioning toward sustainable development and adopting the principles of the green economy. These countries strive to balance economic growth with environmental conservation, and Islamic banking emerges as a viable financial system that can play a significant role in implementing and realizing the implications of the green economy. ASSOCIATE PROFESSOR DR ASHUROV SHAROFIDDIN writes.